The Socio-Political Factors in Jack Kerouac’s Novels (International Journal of Food and Nutritional Sciences, 2022)
The American literature of this era brought forth a new generation out of the war, but the traditional, religious, and social aspects were quite different from those of the previous one. Though the social conditions of the post-war period were traditionalist some of the most furiously discussed writers were homosexuals or bisexuals including Tennessee Williams, Gore Vidal and James Baldwin whose gloomy themes and experimental methods paved way for Beat writers such as Neal Cassady, Allen Ginsberg, William S. Burroughs and Jack Kerouac. Kerouac’s novels are concerned with a desperate situation that captures the various problems in the American society.